A computational model-based study on the exchangeability of hepatic venous pressure gradients measured in multiple hepatic veins. (October 2020) - Wang, Tianqi; Liang, Fuyou; Li, Lei; Zhang, Wen; Wang, Guangchuan; Wang, Jitao; Zhang, Chunqing; Qi, Xiaolong
Highlights: Hepatic venous pressure gradients (HVPGs) measured in the right and middle hepatic veins (HVs) were basically exchangeable. Lower measurement of HVPG in the left HV was caused by the smaller flow proportion. The presence of hepatic vein-to-vein shunts augmented inter-HV HVPG differences. Abstract: Hepatic venous pressure gradient (HVPG) is a hemodynamic index widely used for evaluating the severity of portal hypertension. Theoretically, HVPG can be measured in any of the three major ( i.e., right, middle and left) hepatic veins (HVs); however, it remains unclear whether HVPGs measured in different HVs are exchangeable, and if not, what factors cause inter-HV HVPG differences? In consideration of the potential limitations of invasive in vivo measurements, we employed a computational model implemented in conjunction with stochastic parameter sampling to simulate and compare HVPG measurements in multiple HVs under various sinusoidal portal hypertensive conditions. Results demonstrated that HVPGs measured in the right and middle HVs were basically exchangeable, whereas those in the left HV were relatively lower due primarily to the smaller proportion of hepatic venous flow through the left HV compared with that through the right or middle HV. Moreover, it was found that hepatic vein-to-vein shunts (HVVS) led to a marked augmentation of inter-HV HVPG differences and significant underestimation of portal pressure gradient with HVPG. These findings suggest that understanding the distribution of hepatic venous flow and status of HVVS is essential for selecting a proper HV for implementing HVPG measurement in clinical practice.